2021
DOI: 10.4103/lungindia.lungindia_978_20
|View full text |Cite
|
Sign up to set email alerts
|

High proportion of drug-resistant isolates in adult community-acquired pneumonia from Northeast India

Abstract: Background: Empirical antibiotic therapy is the mainstay of management of adult community-acquired pneumonia (CAP) globally. Knowledge of prevalent pathogen (bacterial) profile and drug susceptibility pattern is very essential for appropriate management of CAP cases, which again calls for regular update of pathogen profile in a given locality. This study was to identify the bacterial etiology of CAP cases and their antibiotic susceptibility pattern. Methods: This cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
3
5
0
Order By: Relevance
“…Based on the etiological agents the predominate bacterial agent causing CAP among adult population in Ethiopia was Klebsiella pneumoniae followed by Streptococcus pneumoniae and Staphylococcus aureus, Escherichia coli, Haemophilus in uenza, and other bacterial species. This nding was similar to a report in Sudan (30), Nigeria (50), Tanzania (49), in Egypt (35), and India (41).…”
Section: Sensitivity Analysissupporting
confidence: 92%
“…Based on the etiological agents the predominate bacterial agent causing CAP among adult population in Ethiopia was Klebsiella pneumoniae followed by Streptococcus pneumoniae and Staphylococcus aureus, Escherichia coli, Haemophilus in uenza, and other bacterial species. This nding was similar to a report in Sudan (30), Nigeria (50), Tanzania (49), in Egypt (35), and India (41).…”
Section: Sensitivity Analysissupporting
confidence: 92%
“…In this meta-analysis, the most common cause of CAP among adult patients in Ethiopia is Klebsiella pneumoniae followed by Streptococcus pneumoniae and Staphylococcus aureus, Escherichia coli , Haemophilus influenzae, and other bacteria. This finding is similar to those reported in Sudan [ 32 ], Nigeria [ 51 ], Tanzania [ 50 ], Egypt [ 37 ], and India [ 43 ]. The overall predominant isolates identified were Klebsiella pneumoniae among HIV infected population suspected with CAP which included in this review.…”
Section: Discussionsupporting
confidence: 91%
“…Meta-analysis results showed that the pooled prevalence of bacterial etiology of CAP among adult patients was 39.18% (36.34–42.02). This report was in line with a study conducted in Sudan 42% [ 32 ] and lower than that in Ghana, 84.5% [ 33 ] Nigeria, 69.6% and 45.2% [ 34 , 35 ], Zambia 59% [ 36 ], Egypt 50.4% [ 37 ], Saudi Arabia 46.6% [ 38 ], Pakistan 75% [ 39 ], in a different region of India, 46.3%, 52.83%, 58.8%, 83% [ [40] , [41] , [42] , [43] ], Bangladesh 61.83% [ 44 ]; a multicenter study in China, 74.4% [ 31 ]; Asian countries, 44.8% [ 11 ] Iran, 44% [ 45 ] Spain, 50.7% [ 46 ] Vietnam, 61.8% [ 47 ] and Ukraine 100% [ 48 ]. This variation may be attributed to differences in the study setting, the characteristics of the study population, and sample size.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is comparable with a previous review reporting the pooled prevalence of bacterial pneumonia in Sudan (33.33%), and a systematic review and meta-analysis of pneumonia in east African children (34%) [ 35 ], Sudan (42%) [ 36 ], Asian countries (44.8%) [ 37 ], Iran (44%) [ 38 ] and India (46.3%) [ 39 ]. On the contrary, the finding of the present systematic review and meta-analysis is massively higher than systematic review and meta-analysis on the pooled magnitude of pneumonia among under-five children in Ethiopia which accounted 18.03 [ 40 ] and lower than the study in Ghana 84.5% [ 41 ], Nigeria 69.6% and 45.2% [ 42 , 43 ], Zambia 59% [ 44 ], Egypt 50.4% [ 45 ], Pakistan 75% (37), in different regions of India 52.83% and 58.8%, 83% [ 46 , 47 ], Bangladesh 61.83% [ 48 ], multicenter study in China 74.4% [ 49 ], Spain 50.7% [ 50 ], and Vietnam 61.8% [ 51 ]. This could be due to differences in the study setting, genetic background of the study population, and sample size.…”
Section: Discussionmentioning
confidence: 99%